408. Benchmarking the Use of New β-lactams Utilizing a Novel Metric of Microbiological Burden. (15th December 2022) - Vivian Tsai, Y; Brandon Bookstaver, P; Kohn, Joseph; Justo, Julie Ann; Justo, Julie Ann; Childress, Darrell; Stramel, Stefanie; Slain, Douglas; Tu, Patrick; Wingler, Mary Joyce B; Jones, Bruce M; Anderson, Daniel; et al.
Abstract: Background: Several methods are used to account for various hospital characteristics when comparing antimicrobial use (AU) between heterogenous hospitals. Recently, a new antimicrobial stewardship metric that adjusts AU by microbiological burden (a-AU) of the bacteria was proposed (Figure 1). It accounts for the resistant phenotypes observed at a given institution, allowing for a more balanced comparison of AU across hospitals. This multicenter retrospective cohort study examined the use of new β-lactams for Gram-negative bacteria (GNB) with difficult-to-treat resistance (DTR) by both AU and adjusted (a-AU) metrics in the southeastern United States. Methods: AU of new β-lactams was determined in 9 hospitals within the Southeastern Research Group Endeavor (SERGE-45) between 2015 to 2020. New β-lactams included ceftolozane/tazobactam, ceftazidime/avibactam, meropenem/vaborbactam, imipenem/cilastatin/relebactam, and cefiderocol. AU was adjusted for prevalence of GNB with DTR including Enterobacterales, Pseudomonas aeruginosa, and Acinetobacter species. DTR was defined as nonsusceptibility to all of the following: cefepime or ceftazidime, levofloxacin or ciprofloxacin, meropenem or imipenem, and piperacillin/tazobactam if tested. Hospitals were ranked by AU and a-AU from lowest to highest. Descriptive statistics were utilized. Results: The cumulative mean AU and a-AU from 2015 to 2020 were 1.96 (range 0.10 to 6.44) and 2.3 (range 0.20 to 8.05) days of therapy (DOT)/1000 patient days, respectively (Figure 2). After adjusting for the prevalence of GNB with DTR, 6 hospitals moved by at least 1 position in ranking (2 hospitals moved up; 4 hospitals moved down) and 1 hospital moved by at least 2 positions in ranking. Conclusion: Overall, the AU of new β-lactams increased after adjusting for the local microbiological burden suggests a potential higher use of antibiotics in relationship to the observed prevalence of GNB with DTR. More than half of the hospitals had a shift in ranking after microbiological adjustment reflecting a more balanced comparison of antibiotic use across heterogenous hospitals. Disclosures: P. Brandon Bookstaver, PharmD, Spero Therapeutics: Advisor/Consultant Julie Ann Justo, PharmD, MS, FIDSA, BCPS-AQ ID, bioMerieux: Honoraria|bioMerieux: Honoraria|Entasis Therapeutics: Advisor/Consultant|Entasis Therapeutics: Advisor/Consultant|Gilead Sciences: Advisor/Consultant|Gilead Sciences: Advisor/Consultant|Merck & Co: Advisor/Consultant|Merck & Co: Advisor/Consultant|Shionogi: Advisor/Consultant|Shionogi Inc.: Advisor/Consultant|Spero Therapeutics: Honoraria|Spero Therapeutics: Honoraria|Vaxart: Stocks/Bonds Julie Ann Justo, PharmD, MS, FIDSA, BCPS-AQ ID, bioMerieux: Honoraria|bioMerieux: Honoraria|Entasis Therapeutics: Advisor/Consultant|Entasis Therapeutics: Advisor/Consultant|Gilead Sciences: Advisor/Consultant|Gilead Sciences: Advisor/Consultant|Merck & Co: Advisor/Consultant|Merck & Co: Advisor/Consultant|Shionogi: Advisor/Consultant|Shionogi Inc.: Advisor/Consultant|Spero Therapeutics: Honoraria|Spero Therapeutics: Honoraria|Vaxart: Stocks/Bonds Bruce M. Jones, Pharm.D., FIDSA, BCPS, AbbVie: Advisor/Consultant|AbbVie: Honoraria|La Jolla: Honoraria|Melinta: Advisor/Consultant|Paratek: Honoraria|Regeneron: Honoraria.